Bacterial Protein Homeostasis Disruption as a Therapeutic Intervention - Khodaparast, Laleh; Wu, Guiqin; Khodaparast, Ladan; Schmidt, Béla Z.; Rousseau, Frederic; Schymkowitz, Joost (Frontiers in Molecular Biosciences, 2021)
Cells have evolved a complex molecular network, collectively called the protein homeostasis (proteostasis) network, to produce and maintain proteins in the appropriate conformation, concentration, and subcellular localization. Loss of proteostasis leads to a reduction in cell viability, which occurs to some degree during healthy aging, but is also the root cause of a group of diverse human pathologies. The accumulation of proteins in aberrant conformations and their aggregation into specific beta-rich assemblies are particularly detrimental to cell viability and challenging to the protein homeostasis network. This is especially true for bacteria; it can be argued that the need to adapt to their changing environments and their high protein turnover rates renders bacteria particularly vulnerable to the disruption of protein homeostasis in general, as well as protein misfolding and aggregation in particular. Targeting bacterial proteostasis could therefore be an attractive strategy for the development of novel antibacterial therapeutics. This review highlights advances with an antibacterial strategy that is based on deliberately inducing aggregation of target proteins in bacterial cells aiming to induce a lethal collapse of protein homeostasis. The approach exploits the intrinsic aggregation propensity of regions residing in the hydrophobic core regions of the polypeptide sequence of proteins, which are genetically conserved because of their essential role in protein folding and stability. Moreover, the molecules were designed to target multiple proteins, to slow down the build-up of resistance. Although more research is required, results thus far allow the hope that this strategy may one day contribute to the arsenal to combat multidrug-resistant bacterial infections.